Karakterisasi Limbah Medis dan Bed Material Pasir Alumina Pada Pembakaran Fluidized Bed\ - Elsha Alvince, Claudia; Suprapta Winaya, I Nyoman; Lokantara, I Putu (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract Handling the problem of medical waste is important to pay attention to, especially during the Covid-19 pandemic. This study shows the right technology to reduce the volume and infectious properties of medical waste are combustion using a fluidized bed reactor, where the characteristics of medical waste contain 47.54% carbon compounds and high volatile content, and have a heating value of 38.147 MJ / kg can be reduced because the waste is in contact with the bed material, it is very easy to treat waste with high moisture content and low calorific value. Also, in this research, 0.8 diameter alumina sand can evenly distribute the temperature in the combustion chamber because it size which is smaller than 1.1 mm can fluidize well and is greater than 0.2 and 0.5 can retain heat better. Keywords: Medical Waste, Combustion, Fluidized Bed, Alumina Sand